Fungal Planet description sheets: 1436 –1477 - Tan Y.P.; Bishop-Hurley S.L.; Shivas R.G.; Cowan D.A.; Maggs-Kölling G.; Maharachchikumbura S.S.N.; Pinruan U.; Bransgrove K.L.; De la Peña-Lastra S.; Larsson E.; Lebel T.; Mahadevakumar S.; et al. (Naturalis Biodiversity Center, 2025)
Novel species of fungi described in this study include those from various countries as follows: Argentina, Colletotrichum araujiae on leaves, stems and fruits of Araujia hortorum. Australia, Agaricus pateritonsus on soil, Curvularia fraserae on dying leaf of Bothriochloa insculpta, Curvularia millisiae from yellowing leaf tips of Cyperus aromaticus, Marasmius brunneolorobustus on well-rotted wood, Nigrospora cooperae from necrotic leaf of Heteropogon contortus, Penicillium tealii from the body of a dead spider, Pseudocercospora robertsiorum from leaf spots of Senna tora, Talaromyces atkinsoniae from gills of Marasmius crinis-equi and Zasmidium pearceae from leaf spots of Smilax glyciphylla. Brazil, Preussia bezerrensis fromair. Chile, Paraconiothyrium kelleni from the rhizosphere of Fragaria chiloensis subsp. chiloensis f. chiloensis. Finland, Inocybe udicola onsoilinmixedforest with Betula pendula, Populus tremula, Picea abies and Alnus incana. France, Myrmecridium normannianum on dead culm of unidentified Poaceae. Germany, Vexillomyces fraxinicola from symptomless stem wood of Fraxinus excelsior. India, Diaporthe limoniae on infected fruit of Limonia acidissima, Didymella naikii on leaves of Cajanus cajan, and Fulvifomes mangroviensis on basal trunk of Aegiceras corniculatum. Indonesia, Penicillium ezekielii from Zea mays kernels. Namibia, Neocamarosporium calicoremae and Neocladosporium calicoremae on stems of Calicorema capitata, and Pleiochaeta adenolobi on symptomatic leaves of Adenolobus pechuelii. Netherlands, Chalara pteridii on stems of Pteridium aquilinum, Neomackenziella juncicola (incl. Neomackenziella gen. nov.)and Sporidesmiella junci from dead culms of Juncus effusus. Pakistan, Inocybe longistipitata on soil in a Quercus forest. Poland, Phytophthora viadrina from rhizosphere soil of Quercus robur, and Septoria krystynae on leaf spots of Viscum album. Portugal (Azores), Acrogenospora stellata on dead wood or bark. South Africa, Phyllactinia greyiae on leaves of Greyia sutherlandii and Punctelia anae on bark of Vachellia karroo. Spain, Anteaglonium lusitanicum on decaying wood of Prunus lusitanica subsp. lusitanica, Hawksworthiomyces riparius from fluvial sediments, Lophiostoma carabassense endophytic in roots of Limbarda crithmoides, and Tuber mohedanoi from calcareussoils. Spain (Canary Islands), Mycena laurisilvae on stumps and woody debris. Sweden, Elaphomyces geminus from soil under Quercus robur. Thailand, Lactifluus chiangraiensis on soil under Pinus merkusii, Lactifluus nakhonphanomensis and Xerocomus sisongkhramensis on soil under Dipterocarpus trees. Ukraine, Valsonectria robiniae on dead twigs of Robinia hispida. USA, Spiralomyces americanus (incl. Spiralomyces gen. nov.) from office air. Morphological and culture characteristics are supported by DNA barcodes.